THE INHERITANCE OF YIELD AND YIELD COMPONENTS OF FIVE WHEAT HYBRID POPULATIONS UNDER DROUGHT CONDITIONS - Nisar Ahmed; Muhammad Aslam Chowdhry; Ihsan Khaliq; Masahiko Maekawa (Indonesian Journal of Agricultural Science, 2007)
The magnitude of genetic inheritance and expected genetic advance are important for the prediction of response to selection in diverse environments and provide the basis for planning and evaluating breeding programs. This work investigated the inheritance of traits related to drought in wheat under natural drought conditions. Cross combinations were made to produce F1 and F2 hybrid populations, which were evaluated in a randomized completed block design with three replications at University of Agriculture, Faisalabad, Pakistan. Six wheat varieties/lines and six derived F2 hybrids were studied to ascertain heritability and genetic advance for plant height, days taken to maturity, number of tillers per plant, spike length, number of grains per spike, 1000-grain weight, and grain yield per plant. Data were collected and subjected to statistical genetic analyses. Heritability estimates and expected genetic advance for plant height, days taken to maturity, number of tillers per plant, 1000-grain weight and grain yield per plant were high for the entire cross combinations while the estimates for spike length and number of grains per spike were relatively low. Our results suggest that improvement for these characters should be faster because of higher heritabilities and greater phenotypic variation. Prospects of genetic improvement for all the characters studied are evident. The most promising cross combinations were WL60 × LU26S and WL61 × LU26S. These traits, therefore, deserve better attention in future breeding programs for evolving better wheat for stress environments.